2002
DOI: 10.1124/jpet.301.3.908
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Activation of p42/44 Mitogen-Activated Protein Kinase and c-Jun N-Terminal Kinase by Acetaldehyde in Rat Hepatocytes and Its Loss after Chronic Ethanol Exposure

Abstract: Several cell-damaging effects of ethanol are due to its major metabolite acetaldehyde but its mechanisms are not known. We have studied the effect of acetaldehyde on p42/44 mitogenactivated protein kinase (MAPK) and p46/p54 c-Jun N-terminal kinase (JNK 1/2) in rat hepatocytes. Acetaldehyde caused peak activation of p42/44 MAPK at 10 min followed by JNK activation at 1 h. These responses were acetaldehyde dose-dependent (0.2-5 mM). There was a consistently higher activation of p46 JNK than p54 JNK. Ethanol also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
6
21
0
Order By: Relevance
“…Hepatocytes express two JNK genes (JNK1 and JNK2) and bile acids cause activation of both JNK1 and JNK2, but JNK1 activation causes apoptosis whereas JNK2 activation protects against apoptosis [21] . It has been reported that ethanol causes more pronounced activation of JNK 1 compared to JNK 2, suggesting a role for this preferential activation of JNK 1 in ethanol-induced apoptosis of hepatocytes [15] .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Hepatocytes express two JNK genes (JNK1 and JNK2) and bile acids cause activation of both JNK1 and JNK2, but JNK1 activation causes apoptosis whereas JNK2 activation protects against apoptosis [21] . It has been reported that ethanol causes more pronounced activation of JNK 1 compared to JNK 2, suggesting a role for this preferential activation of JNK 1 in ethanol-induced apoptosis of hepatocytes [15] .…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that ethanol activates MAPKs [1,2] , and acute exposure of primary cultured rat hepatocytes to ethanol for 60 min increases the activities of p42/44 MAPK and p-JNK1/2, with both activities gradually decreasing thereafter [15] . Exposure to ethanol has been shown to cause prolonged activation of p-JNK1/2; however, this response was attenuated in hepatocytes obtained from rats chronically exposed to ethanol for 6 wk [16] .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…MAPKs regulate various biological processes including cell growth, proliferation, movement, inflammation, fatty degeneration, necrosis and apoptosis [70]. In a primary culture of rat hepatocytes, ethanol showed modest activation of ERK1/2 and notable activation of JNK [71]. In rat cultured hepatocytes, when ERK1/2 phosphorylation was inhibited by U-0126 (a MEK1/2 inhibitor), phosphorylation of JNK by ethanol was increased [72].…”
Section: Some New Findings With Effects Of Ethanol-induced Oxidative mentioning
confidence: 99%